2015
DOI: 10.1088/0953-4075/48/7/071001
|View full text |Cite|
|
Sign up to set email alerts
|

Separation of single-and two-center interference in ionization of H2by proton impact

Abstract: We present a triple differential experimental study of ionization of molecular hydrogen by proton impact. By comparing cross-sections obtained for coherent and incoherent projectile beams we were able to extract contributions from interference. Two types of distinctly different interferences could be identified. We demonstrate that both types can be separated in the same data set by analyzing triple differential cross-sections for fixed momentum transfer and for fixed recoil-ion momentum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 17 publications
2
43
0
Order By: Relevance
“…[1]). The present work is an attempt to relate the results of Karlovets et al to those obtained in the past five years in the investigations of the projectile beam coherence effects in ion-atom and ion-molecule collisions [4][5][6][7][8][9][10][11][12][13]. It is an interesting question whether the formulas of Karlovets et al predict a similar wave packet effect in scattering of energetic ions as in the case of electron impact.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…[1]). The present work is an attempt to relate the results of Karlovets et al to those obtained in the past five years in the investigations of the projectile beam coherence effects in ion-atom and ion-molecule collisions [4][5][6][7][8][9][10][11][12][13]. It is an interesting question whether the formulas of Karlovets et al predict a similar wave packet effect in scattering of energetic ions as in the case of electron impact.…”
mentioning
confidence: 67%
“…This effect may influence the results of FDCS measurements in the field of ion-atom collisions. The dependence of the FDCS on the projectile coherence has already been investigated experimentally [6,8,10,12,13] and theoretically [11,22]. One of the goals of the investigations was to solve the so-called C 6+ puzzle, a discrepancy between the measured and theoretical FDCSs for the single ionization of He by 100 MeV/nucleon C 6+ projectiles [23], which has remained unexplained for more than a decade.…”
Section: (Cm)mentioning
confidence: 99%
“…In contrast, for η close to unity by now there is an extensive literature on experimental and theoretical studies [e.g. [15][16][17][18]20,26,27] supporting the interpretation that scattering cross sections can be significantly affected by the projectile coherence properties. In this regime, experimental studies now enter a phase in which such coherence effects are used as a tool to sensitively investigate the few-body reaction dynamics.…”
mentioning
confidence: 89%
“…An example is molecular two-center interference, which has been observed in numerous experimental studies and predicted by theory for charged particles colliding with diatomic molecules [e.g. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. There, the diffracted projectile waves originating from the two atomic centers interfere with each other.…”
Section: Introductionmentioning
confidence: 99%
“…However, this assertion was rebutted by Sharma et al [22], who demonstrated that there were no noticeable differences in the beam divergence for the two slit distances. Later, resolution-independent coherence effects were reported for various processes and targets for projectiles with relatively small speed and large perturbation parameters η (projectile charge to speed ratio) [19,20,23,24, for a review see 25].…”
Section: Introductionmentioning
confidence: 99%